Analisis Kepuasan Konsumen Terhadap Produk Dan Pelayanan Seblak Rorongkong Teh Memey Kota Bogor - Putri Sakti Fujiyanti A.; Raisa Fasya; Viona Kesya Sundari; Ghaisya Raihana; Ilham Fauzi; Khoirul Aziz Husyairi; Tina Nur Ainun; Ai Imas Faidoh Fatimah (Jurnal Sains Indonesia, 2023)
This research is based on the tendency of consumers to consume spicy food in Bogor City, namely Seblak. Seblak is a spicy food that is in great demand by teenagers to adults. Seblak comes from the word "nyeblak" which means "shocking". One of the various ways to observe consumers' wants and needs for seblak is to analyze the satisfaction of customers visiting the Seblak Rorongkong Teh Memey Shop in Bogor City. The method used in analyzing consumer preferences for seblak shop is Importance Performance Analysis (IPA). This method is applied in order to rank various attributes and identify the efforts that need to be made by the seblak shop in making improvements. Data collection was carried out using a questionnaire to 100 respondents with an age range of 17-35 years. The data obtained was analyzed to produce attributes that have a level of compatibility between the level of importance and level of performance which was then analyzed using a Cartesian diagram to observe the level of importance and level of performance of Kedai Seblak Rorongkong Teh Memey. The results of the analysis will be applied to determine the right strategies and corrective actions to improve the performance of the seblak shop.